Pengaruh Pelatihan Rasional Emotif Perilaku terhadap Penurunan Perilaku Kecurangan Akademik Siswa - Andhika Fajar Wasesa; R. Rachmy Diana (JIP (Jurnal Intervensi Psikologi), 2016)
This study aims to determine the effect of the Rational Emotive Behavior Training to reduce academic cheating behavior in students. Subjects in this study were ten students aged 13-15 years and have academic cheating behavior score from moderate to high. The design used was one group pretest-posttest. Collecting data in this study was conducted using a scale of academic cheating compiled by researchers. Data analysis method used is non-parametric statistical techniques by using Wilcoxon Signed-Rank Test to test for differences in the data score pre test and post test. Results of the analysis showed the value of Z when the post test for - 677a with p equal to 0,498. It can be concluded that the training of Rational Emotive Behavior (REBT) is not effectively used to derive academic cheating behavior in students in junior high school "X" in Yogyakarta. Keywords: Rational Emotive Behavior Training, Academic cheating behavior